2019
DOI: 10.13058/raep.2019.v20n1.1070
|View full text |Cite
|
Sign up to set email alerts
|

A influência de Atividades Extracurriculares no Desenvolvimento de Competências Gerenciais em Grupos de Pesquisa

Abstract: Este estudo visou identificar relações entre atividades extracurriculares (AE) e domínio de competências gerenciais (CG) em grupos de pesquisa (GP) brasileiros com uso da escala de domínio de CG em GP desenvolvida por Freitas e Odelius (2017), juntamente com questões relativas à contribuição de AE para o desenvolvimento de CG em GP. O questionário eletrônico foi aplicado a 528 participantes e submetido a estatísticas descritivas, análise de correlação Kendall-tau b e teste Kruskal-Wallis. A análise dos dados p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
1
0
3
Order By: Relevance
“…Among the various national and international studies conducted in the last decade, it was identified that those that address managerial competencies deal with: influences of contextual aspects on competencies (Barbosa, Mendonça & Cassundé, 2016;Lan & Hung, 2018); relationship of the managerial competencies construct with other variables (Brandão et al, 2012;Bucur, 2013;Cassol, Cintra, & Ruas, 2016;Freitas, Montezano, & Odelius, 2019;Lara & Salas-Vallina, 2017;Trivellas & Reklits, 2014;Verle et al, 2014); identification of management skills relevant to specific sectors (Ésther, 2011;Gloria Jr. et al, 2014;Liang, Howard, Leggat, & Bartram, 2018;Salles & Villardi, 2017;Surdiman et al, 2019); comparison between the levels of competence demonstrated by public and private managers (Pillay, 2008;Chong, 2013), technicians or politicians (Losada & Esteve, 2018) and different professional formations (Godoy & D'Amélio, 2012); development of MC scales for different contexts (Brandão et al, 2010;Bündchen et al, 2011;Comin, Severo, Dall Agnol, Medeiros, & Guimarães, 2017;Freitas & Odelius, 2017;Santos, 2014); in addition to more theoretical studies aimed at understanding the concept or its different classifications (Freitas & Odelius, 2018).…”
Section: Managerial Competencies In the Public Sectormentioning
confidence: 99%
“…Among the various national and international studies conducted in the last decade, it was identified that those that address managerial competencies deal with: influences of contextual aspects on competencies (Barbosa, Mendonça & Cassundé, 2016;Lan & Hung, 2018); relationship of the managerial competencies construct with other variables (Brandão et al, 2012;Bucur, 2013;Cassol, Cintra, & Ruas, 2016;Freitas, Montezano, & Odelius, 2019;Lara & Salas-Vallina, 2017;Trivellas & Reklits, 2014;Verle et al, 2014); identification of management skills relevant to specific sectors (Ésther, 2011;Gloria Jr. et al, 2014;Liang, Howard, Leggat, & Bartram, 2018;Salles & Villardi, 2017;Surdiman et al, 2019); comparison between the levels of competence demonstrated by public and private managers (Pillay, 2008;Chong, 2013), technicians or politicians (Losada & Esteve, 2018) and different professional formations (Godoy & D'Amélio, 2012); development of MC scales for different contexts (Brandão et al, 2010;Bündchen et al, 2011;Comin, Severo, Dall Agnol, Medeiros, & Guimarães, 2017;Freitas & Odelius, 2017;Santos, 2014); in addition to more theoretical studies aimed at understanding the concept or its different classifications (Freitas & Odelius, 2018).…”
Section: Managerial Competencies In the Public Sectormentioning
confidence: 99%
“…De acordo com Freitas et al (2019), a maioria das atividades extracurriculares são capazes de proporcionar o desenvolvimento de competências gerenciais importantes para o contexto de grupos de pesquisa, além de influenciar o domínio de competências gerenciais em outros contextos.…”
Section: O Ensino E As Atividades Extracurricularesunclassified
“…Consiste em um relato de experiência de acadêmicos do 9º semestre do curso de O identificado corrobora com estudos 7,8,9,10,11 que tem buscado comprovar não apenas a existência do saber sobre plantas medicinais, como também justificar a importância de se estudar este assunto, discutindo não apenas em nível acadêmico, como também profissional e comunidade, destacam-se nesses estudos que, apesar de saber sobre identificação e uso de uma larga variedade de plantas medicinais, muitos idosos não consideram os riscos envolvidos no uso das plantas, seja pela forma de preparo inadequada ou pelo uso concomitante a medicações.…”
Section: Metodologiaunclassified